A Comparative Study of the English Language Performance of Islamic Studies and Education Students in KIRKHS and INSTED - Rashid, Adnan bin Abd (ASPENSI in Bandung, Indonesia, 2011)
ABSTRACT: The research is a comparative study of the English language performance among Islamic studies or Education students in the Kulliyyah of Islamic Revealed Knowledge and Human Science (KIRKHS) and the Institute of Education (INSTED). The main aim of the research is to observe how the undergraduate students perform in the English language and to examine the standard of English language performance for both kulliyahs. The respondents of this study were taken from the Kulliyyah of IRKHS and the INSTED, both at the IIUM (International Islamic University of Malaysia). According to the figures obtained from the Centre for Languages and Pre-university Academic Development (CELPAD) of the IIUM, it was revealed that many of Islamic studies students were dubbed poor performers in English language. Evidently, the average scores for English language courses were C plus and C as shown by the statistics from CELPAD. The result of study shows that the majority of the respondents considered themselves as competent in terms of English language as compared to other languages, and they indicated that their English competence was mostly sufficient for their academic activities. And finally, the respondents indicated that they would like to improve their English language competence. Key words: Comparative study, English language performance, Islamic studies or Education students, poor performers, and to improve their English language competence.Â Â About the Author: Assoc. Prof. Dr. Adnan bin Abd Rashid is Senior Lecturer at the Institute of Education IIUM (International Islamic University of Malaysia), Jalan Gombak, 53100 Kuala Lumpur, Malaysia. He is Programme Specialist and Expert in education ISESCO, Rabat, Morocco. For academic purposes, he can be reached at: adnan@iiu.edu.my and arashid@isesco.org.maHow to cite this article? Rashid, Adnan bin Abd. (2011). âA Comparative Study of the English Language Performance of Islamic Studies and Education Students in KIRKHS and INSTEDâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.4, No.1 [Mei], pp.49-66. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-0112. Chronicle of article: Accepted (March 13, 2011); Revised (April 16, 2011); and Published (May 20, 2011). Â Â